Prevalence of low bone mass among adolescents with nontransfusion-dependent hemoglobin E/β-thalassemia and its relationship with anemia severity - Pairunyar Nakavachara (2018)
© 2017 Wiley Periodicals, Inc. Background: Low bone mass is common among adolescents with transfusion-dependent β-thalassemia despite adequate transfusion and iron chelation. However, there are few reports regarding bone mineral density (BMD) among adolescents with nontransfusion-dependent thalassemia (NTDT). Indeed, only BMD data in patients with nontransfusion-dependent (NTD) β-thalassemia intermedia have been reported. No previous study has investigated BMD among adolescents with NTD hemoglobin (Hb) E/β-thalassemia. Objective: To determine the prevalence of low bone mass among adolescents with NTD Hb E/β-thalassemia and factors relating to low bone mass. Methods: We investigated BMD of lumbar spine (L2–L4; BMDLS) and total body (BMDTB), as measured by dual-energy X-ray absorptiometry, in 22 adolescents (aged 13.2–20 years) with NTD Hb E/β-thalassemia. Results: Low bone mass was found to be 18.2% and 22.7% at the lumbar spine (BMDLS Z-score adjusted for bone age and height age) and 13.6% and 9.1% at the total body (BMDTB Z-score adjusted for bone age and height age). Patients with mean Hb level <8 g/dl were more likely to have low bone mass (BMDLS and BMDTB Z-scores adjusted for bone age) compared to those with Hb level ≥ 8 g/dl. Mean Hb level correlated with BMDLS and BMDTB Z-scores adjusted for bone age. Conclusion: We demonstrated that a low Hb level was associated with low bone mass among adolescents with NTD Hb E/β-thalassemia. A significant proportion of low bone mass among these patients highlights the importance of appropriate management, including red cell transfusion, vitamin D and calcium supplementation for improved long-term bone health.